The cultural construction of the feminine through Disney’s films - Afina Murtiningrum; Destary Praptawati; Riana Permatasari (EduLite: Journal of English Education, Literature and Culture, 2023)
The question of gender roles in Disney’s films has been one of the relevant issues in their industry. Disney has for a long time been at battle with the public for being accused of depicting their characters, specifically females, in stereotypical ways. Gender roles can affect viewers in the manner they see themselves with the others around them. The roles of men and women pictured in Disney’s films have mirrored the cultural perspective and beliefs of social norms and expectations on gender roles and identity. This study tries to figure out the roles of the princesses and the female villains in Disney's films with regard to the cultural construction of the feminine. This study applied qualitative  descriptive  method with several steps taken during the data analysis. Finally,  the  analysis  was  informally presented  through  a descriptive representation in words. The findings demonstrate that despite displaying the characteristics of strength and power, female villains are frequently portrayed as ugly, overweight, or nonsymmetrical. On the other hand, the princesses are shown to be very beautiful, which helps them succeed in life. The portrayal of the female villains also promotes the notion that powerful women are the most dangerous people in the world. In general, Disney has not yet achieved gender equation between villains and princesses. There is little room for girls to choose between being a wicked villain and a pretty princess.